Improving Service Quality in Vehicular ad hoc Network using Content-Based Scheduling and Routing - Iraj Rezaei, Abbas Karimi and Faraneh Zar Afshan (International Journal of Advanced Science and Technology, 2020)
Vehicular ad hoc network is a special case of mobile ad hoc network in which vehicles are considered as mobile nodes. This type of wireless network is considered as one of the most important bases for the formation of intelligent transportation system and then smart city. Therefore, it is natural that the optimal performance of this network can be effective in improving the planning and management processes of smart cities. In this paper, the issue of improving the performance of a vehicular ad hoc network from the point of view of scheduling is discussed. Accordingly, this paper discusses the use of message scheduling techniques to improve the quality of service on the network and provides a message scheduling mechanism to increase service quality and reduce the likelihood of accidents in the intelligent transportation system. The proposed method categorizes data at the network level based on their content into different scheduling queues and produces a content-based topological structure for each type of data. The proposed algorithm seeks to reduce the likelihood of an accident as well as road traffic by providing a new way to exchange emergency messages on vehicular ad hoc network. Based on the results of the experiments, the proposed algorithm will reduce the packet loss rate and end-to-end latency in the vehicular ad hoc network compared to the current techniques used. The great advantage of the proposed algorithm is the simplicity of calculations and its speed in choosing the right activity to improve network performance.